Laveran décalé - GOOSSENS, Pierre L (Médecine tropicale et santé internationale, 2023)
Unconventional LaveranCharles Louis Alphonse Laveran - 18 June 1845 - 18 May 1922: first French Nobel Prize in Medicine, in recognition of his work on the role played by protozoa in causing “diseases”. One hundred years after his death, only written records remain of his work and life. The witnesses to this period are no more. Alphonse Laveran has become an “object” of history.He was deeply involved in a turbulent historical period, marked by crises of regime change (Monarchy/Empire/Republic), military events (French colonial expansion in North Africa from 1830, the wars of 1870 and 1914-1918) and their consequences (the medical impact of infections in the colonial empire and during armed conflicts, the Dreyfus affair, among others), the advent of Pasteurian “microbiology” and the deciphering of the causes and modes of transmission of infectious diseases. A player on the edge of the military and civilian worlds, with their own, sometimes incompatible, visions of the aims and objectives to be pursued, Alphonse Laveran lived through these upheavals in a society in the throes of change, in his family and scientific environment.Paradoxically, the primary sources available to us for learning about this scientist and man are both abundant and “scarce” for us in the 21st century. His scientific publications and many of his speeches at various academies, committees and meetings are for the most part public and accessible, giving us a vision of a professional in scientific and medical research in action, presenting and convincing people of his ideas and theoretical and practical insights. The writings of his contemporaries, both public and private, shed light on - distort? - the man’s many facets. On the other hand, there are few surviving sources on the man and his vision of life, his life and that of his family and friends.We will rely on the archives that have been preserved, in particular by the organisations that welcomed him during his military and civilian career, as well as by his wife Marie Laveran and his colleague Marie Phisalix, one of the first doctors of medicine in France and a renowned herpetologist. These two female figures have preserved and contributed to his memory. Let’s take a closer look at the man behind the scientist, as we can imagine him through the traces that remain.Laveran décaléCharles Louis Alphonse Laveran : 18 juin 1845 – 18 mai 1922. Premier prix Nobel de médecine français, « en reconnaissance de ses travaux sur le rôle joué par les protozoaires dans l’apparition des maladies ». Cent ans après sa disparition ne restent plus que des traces écrites de ses travaux et de sa vie. Les témoins de cette période ne sont plus. Alphonse Laveran est devenu un « objet » d’Histoire.Il fut un acteur profondément intégré dans une période historique mouvementée, marquée par des crises de changement de régime (Monarchie/Empire/République), par des événements militaires (expansion coloniale française en Afrique du Nord depuis 1830, guerres de 1870 et 1914-1918) et leurs conséquences (impact médical des infections dans l’empire colonial et lors des conflits armés, affaire Dreyfus entre autres), par l’avènement de la « microbiologie » pasteurienne et le déchiffrement des causes et modes de transmission des maladies infectieuses. Acteur à la lisière des mondes militaire et civil, avec leurs propres visions des buts et objectifs à suivre, parfois incompatibles, Alphonse Laveran vécut ces bouleversements dans une société en plein changement, dans son milieu familial et scientifique.Les sources primaires à notre disposition pour aborder ce personnage scientifique, et cet homme, sont paradoxalement à la fois abondantes et « pauvres » pour nous, curieux du XXIe siècle. Ses publications scientifiques et nombre de ses interventions dans les différentes académies, comités et réunions sont pour la plupart publiques, accessibles et nous donnent une vision du professionnel de la recherche scientifique et médicale en action pour présenter et convaincre de ses idées et fulgurances théoriques et pratiques. Les écrits de ses contemporains, qu’ils soient publics ou privés éclairent – et déforment ? - de multiples facettes du personnage. A l’opposé, peu de sources persistent quant à l’homme et sa vision de la vie, de sa vie et celle de sa famille et de ses proches.Nous nous appuierons sur les archives qui ont été conservées, en particulier par les structures et corps l’ayant accueilli au cours de sa carrière militaire et civile, ainsi que par son épouse Marie Laveran et sa collègue Marie Phisalix, une des premières docteures en médecine en France et herpétologiste de renom ; ces deux personnalités féminines ont préservé et contribué à son souvenir. Nous tenterons d’approcher l’homme derrière le scientifique, tel que nous pouvons l’imaginer à travers les traces qui nous restent.